2011
DOI: 10.1589/jpts.23.923
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure Distribution During Walking: Comparison of Subjects with and without Chronic Low Back Pain

Abstract: Abstract.[Purpose] The purpose of this study was to investigate changes during walking in plantar pressure distribution on both the affected and unaffected sides of patients with chronic low back pain (LBP).[Subjects] Sixty subjects were included in this study, including 30 patients with chronic low back pain and 30 healthy individuals as the control group.[Methods] The plantar foot pressure and the trajectory of the center of pressure (COP) of both groups were measured using the F-scan System while they walke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…in which no significant differences were found in plantar pressure distribution parameters in patients with low back pain. 5 In the current study, the PWS of LSS group was lower than control group. It's indicated that walking slowly with shorter step length might be the reason of these results in patients with pain.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…in which no significant differences were found in plantar pressure distribution parameters in patients with low back pain. 5 In the current study, the PWS of LSS group was lower than control group. It's indicated that walking slowly with shorter step length might be the reason of these results in patients with pain.…”
Section: Discussionmentioning
confidence: 40%
“…1 Several investigators reported that patients with LSS may often have decreased walking speed due to the pain. [5][6][7] As such, patients with LSS experience alteration in walking pattern resulting from abnormal transmission of the forces from the upper body to lower body which may cause to alteration in plantar pressure distribution at the foot. 8 Walking is obviously critical for physical activity and performance for everyday life, and thus ambulation limitation is a severe health marker to be monitored.…”
mentioning
confidence: 99%
“…Lee et al 14 ) utilized posturography for the comparison of patients with LBP with a control group of healthy individuals. In their study, they mainly found significant differences in A-P excursion of COF between patients and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Gait is a complex process that involves the nervous and musculoskeletal systems. It is the repetitive and continuous motion which moves the body forward while maintaining a stable state during the stance phase 11 ) , and the physical activities of upright gait connect the lower limb joints and the spine, the central pillar of the trunk, in a kinetic chain, mutually influencing each other 12 ) . The role of the spine is essential in normal gait and spinal deformation affects the normal gait pattern 13 ) , which provides important information for the treatment of patients with walking problem through gait pattern analysis 14 ) .…”
Section: Introductionmentioning
confidence: 99%